New Bruce-ladder multiplex PCR assay for the biovar typing of Brucella suis and the discrimination of Brucella suis and Brucella canis - López-Goñi, Ignacio (2011)
Rapid and specific identification of Brucella suis at the biovar level is necessary because some of the biovars that infect animals are pathogenic for humans. None of the molecular typing methods described so far are able to discriminate B. suis biovars in a single test and differentiation of B. suis from Brucella canis by molecular approaches can be difficult. This article describes a new multiplex PCR assay, Suis-ladder, for fast and accurate identification of B. suis at the biovar level and the differentiation of B. suis, B. canis and Brucella microti. An advancement of the original Bruce-ladder PCR protocol which allows the correct discrimination of all known Brucella species is also described.